2004
DOI: 10.1007/s00787-004-0410-2
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of symptoms of attention-deficit/hyperactivity disorder and oppositional defiant disorder in school age children in Turkey

Abstract: The prevalence of ADHD and ODD in primary school children was not considered to be small. Studies concerning the distribution of symptoms in different societies, cultures, and viewpoints and identification of children with this type of problem are beneficial for early diagnosis and prophylactic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
56
2
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 22 publications
16
56
2
10
Order By: Relevance
“…It is important to note however that none of these studies employed the present methodology of a population-based random sample, as this method would be prohibitive because the cities cited earlier in this paper range in population from about 135,000 to over 13,000,000. The ADHD prevalence rate in the present study was also similar to studies conducted in the Middle East and Far East, for example, the ADHD prevalence rate was 8.1% in Turkey (Ersan, Dogan, Dogan, & Sumer, 2001), 9.4% in Qatar (Bener, Al Qahtani, & Abdelaal, 2006), and 8.9% in China (Leung et al 1996).…”
Section: Discussionsupporting
confidence: 88%
“…It is important to note however that none of these studies employed the present methodology of a population-based random sample, as this method would be prohibitive because the cities cited earlier in this paper range in population from about 135,000 to over 13,000,000. The ADHD prevalence rate in the present study was also similar to studies conducted in the Middle East and Far East, for example, the ADHD prevalence rate was 8.1% in Turkey (Ersan, Dogan, Dogan, & Sumer, 2001), 9.4% in Qatar (Bener, Al Qahtani, & Abdelaal, 2006), and 8.9% in China (Leung et al 1996).…”
Section: Discussionsupporting
confidence: 88%
“…However, the prevalence we found was higher than that of other prevalence studies carried out in Turkey in different years. A study conducted by Gul et al, 32 for instance, reported a prevalence of 8.6% and another one, reported by Ersan et al, 33 found a prevalence of 8.1%. Güler et al, 34 by contrast, reported a prevalence of 2.7-9.6% based on parent assessment and 2-10.1% based on teacher evaluation.…”
Section: Discussionmentioning
confidence: 90%
“…The global subtype studies reported that the combined and the inattentive types were the most common, 24,25 while two epidemiological studies from Turkey found that the hyperactive type was the most common. 32,33 These differences in the rates of various subtypes may stem from methodological variations as well as cultural discrepancies. More society-based studies are needed to interpret our results with respect to subtype distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Pierrehumbert et al [8] reported no difference in the prevalence of ADHD symptoms in school-aged Swiss children between parent (8.0%) and teacher (9.6%) evaluations, using the clinical cutoff point for the ADHD index. Erşan et al [10] found no significant difference in ADHD symptoms of school-aged Turkish children, using DSM-IV criteria, based on parent (9.6%) and teacher (7.3%) evaluations. Furthermore, Polanczyk and Jensen [7] retrieved 71 studies during a recent systematic review of epidemiological studies on ADHD published in the last decade.…”
Section: Discussionmentioning
confidence: 97%